Tsunami Evacuation Route Modeling (Study in Karang City and Karang Raya Village City) - Sulaeman D; Nurhasanah A; Aprizal Aprizal (International Conference on Engineering and Technology Development (ICETD), 2017)
Kota Karang Village and Kota Karang Raya Village are two urban villages located in the coastal city of Bandar Lampung and are vulnerable to tsunami threats. The tsunami threat comes from the possible subduction of the Indo Australia Plate and the Eurasian Plate as well as the volcanic activity of Mount Anak Krakatau. The two villages are inhabited by 16.726 people with a high density of 29.344 people per km2 and occupy an area of 0,57 km2 with an average height of 10 meters. The dense population and moderate contours left both villages potentially causing casualties in the event of a tsunami disaster. Therefore, a study on the optimization of the tsunami evacuation route in both urban villages is needed. The method used in this research is to conduct a review of the tsunami evacuation route through analysis of population data and topographic data which will then become evacuation simulation input using Evacuware software. The data included in the form of population data by sex and age and topographic data in the form of situation map and evacuation route map. The simulation is done with two scenarios, the first scenario uses two Temporary Evacuation Sites namely Mount Mastur and Dwipangga Park. The second scenario conducted by placing four additional vertical shelter using three reconstructed primary schools and one reconstructed community health center